Metabolic Remodeling in the Pressure‐Loaded Right Ventricle: Shifts in Glucose and Fatty Acid Metabolism—A Systematic Review and Meta‐Analysis - Anne‐Marie C. Koop; Guido P. L. Bossers; Mark‐Jan Ploegstra; Quint A. J. Hagdorn; Rolf M. F. Berger; Herman H. W. Silljé; Beatrijs Bartelds (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Right ventricular (RV) failure because of chronic pressure load is an important determinant of outcome in pulmonary hypertension. Progression towards RV failure is characterized by diastolic dysfunction, fibrosis and metabolic dysregulation. Metabolic modulation has been suggested as therapeutic option, yet, metabolic dysregulation may have various faces in different experimental models and disease severity. In this systematic review and meta‐analysis, we aimed to identify metabolic changes in the pressure loaded RV and formulate recommendations required to optimize translation between animal models and human disease. Methods and Results Medline and EMBASE were searched to identify original studies describing cardiac metabolic variables in the pressure loaded RV. We identified mostly rat‐models, inducing pressure load by hypoxia, Sugen‐hypoxia, monocrotaline (MCT), pulmonary artery banding (PAB) or strain (fawn hooded rats, FHR), and human studies. Meta‐analysis revealed increased Hedges’ g (effect size) of the gene expression of GLUT1 and HK1 and glycolytic flux. The expression of MCAD was uniformly decreased. Mitochondrial respiratory capacity and fatty acid uptake varied considerably between studies, yet there was a model effect in carbohydrate respiratory capacity in MCT‐rats. Conclusions This systematic review and meta‐analysis on metabolic remodeling in the pressure‐loaded RV showed a consistent increase in glucose uptake and glycolysis, strongly suggest a downregulation of beta‐oxidation, and showed divergent and model‐specific changes regarding fatty acid uptake and oxidative metabolism. To translate metabolic results from animal models to human disease, more extensive characterization, including function, and uniformity in methodology and studied variables, will be required.